Geometrical study of Middle Kingdom funerary complexes in Qubbet el-Hawa (Aswan, Egypt) based on 3D models - Antonio Mozas-Calvache; José Luis Pérez-García; José Miguel Gómez-López (Virtual Archaeology Review)
Highlights: